A socio-legal study of non-defendant character evidence in criminal trials - Thomason, Matt (2020)
This thesis presents a socio-legal analysis of the use of non-defendant character evidence in Crown Court criminal trials. Combining an in-depth doctrinal analysis of s.100 of the Criminal Justice Act 2003 and s.41 of the Youth Justice and Criminal Evidence Act with original qualitative empirical methods (interviews with trial counsel and observations of real Crown Court trials), the thesis explores the real-life practical operation of these two rules of exclusion and their associated inclusionary exceptions, and how these rules influence the pre-trial process and eventual trial tactics of counsel. The findings suggest that: confusion as to the scope of s.100 and s.41 are causing problems in practice; most character evidence is admitted via agreement following negotiations between the adversarial parties; and funding cuts combined with increased time pressures result in a lack of procedural compliance. The thesis concludes by setting the findings in a broader context of increasing managerialism throughout the criminal process.